Characteristics, Comfort Level and Success in Chronic Kidney Disease Patients Undergoing Continuous Ambulatory Peritoneal Dialysis Therapy and its Review according to Islamic View - Kartika Dwi Suryani; Linda Armelia; Muhammad Arsyad (Junior Medical Journal, 2022)
Chronic Kidney Disease (CKD) is a disease that is a big problem in the world. The results of a survey by the Indonesian Nephrology Association (PERNEFRI) estimated that around 12.5% of the Indonesian population had decreased kidney function. Currently, there are still many CKD patients who are not familiar with CAPD so that there is not much data regarding the description of CAPD satisfaction in Indonesia. The purpose of this study was to examine the characteristics of CKD patients using CAPD therapy and the level of comfort and success in CAPD. The type of research method chosen is Cross Sectional, which is a form of descriptive study that aims to get an overview of the prevalence of a population. The population of this study were patients CKD who underwent CAPD at Hermina Hospital Bekasi from January to March 2022. Data analysis was carried out using univariate analysis. The results showed that 45 CKD patients using CAPD in Bekasi were some of the subjects, the majority of whom were male (60%), the most age ranged from 20-60 years (95.56%), the most comorbid was hypertension (35.6%), and the majority had undergone CAPD therapy for 1-3 years (48.89%). At the level of comfort in using CAPD, most of the respondents answered quite comfortable (53.3%) and 100% of the subjects would recommend the use of CAPD. In general, there was a decrease in uric acid and creatinine levels, as well as an increase in LGF within 3 months of data collection in subjects. As well as the command of Allah SWT to always be patient and try while undergoing treatment.